دراسة تأثير الحرارة والمحاليل الكيميائية على التوصيلية الحرارية (K) لراتنج البولي أستر غير المشبع - محمد, عواطف عذاب (Al-Nahrain Journal of Science, 2009)
In this research Unsaturated Polyester resin was used as a matrix for composite material with glass fiber and carbon as reinforcement's materials with different volume fraction (10%